The Artistic Imaging in the Poetry of Ibrahim AbuTaleb - یداللهي فارساني عباس (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The present research is an attempt in studying and analyzing the topic of the artistic imaging and its most important manifestations in the poetry of Ibrahim AbuTaleb- a Yemeni contemporary poets - by relying on an analytical descriptive method, presenting its samples and analyzing its function in his poetry. Eventually this study has come to this conclusion that this poet has used artistic imaging representations as an effective tool to express his internal thoughts and perceptions to depict the reality of the Yemeni contemporary society in a modern coverage of heritage. Among the manifestations of artistic imaging in the poetry of this poet we can refer to the following topics: myth, symbol, heritage, Sufism, reality and national heritage.